Mathematical model of thrombin generation and bleeding phenotype in Amish carriers of Factor IX:C deficiency vs. controls. Issue 182 (October 2019) - Gupta, S.; Bravo, M.C.; Heiman, M.; Nakar, C.; Brummel-Ziedins, K.; Miller, C.H.; Shapiro, A.
Abstract: Introduction: Factor IX:C (FIX:C) levels vary in hemophilia B carriers even in pedigrees with a unifying genetic defect. Analyzing the balance between pro-and anticoagulants might increase our understanding of carriers' bleeding potential. Aim: In this research study, we evaluated bleeding scores (BS) and a novel mathematical model of thrombin generation (TG) in Amish FIX:C deficient carriers and controls. Methods: Blood samples and BS were obtained from post-menarchal females, including 59 carriers and 57 controls from the same extended pedigree. Factors II, V, VII, VIII, IX, X, antithrombin, tissue factor pathway inhibitor and protein C were assayed to generate mathematical models of TG in response to 5pM tissue factor (TF) and for TF + thrombomodulin. BS was based on a modification of the MCMDM-1VWD scoring system. Results: Carriers had a lower mean FIX:C (68% vs. 119%), von Willebrand factor antigen (108 vs.133) and Tissue activatable fibrinolysis inhibitor (103 vs. 111) compared to controls; both groups had a similar mean BS. Carriers demonstrated significantly lower TG parameters on both mathematical models compared to controls. Carriers with FIX:C ≤ 50% had lower TG curves than those >50% but similar BS. Conclusion: Thrombin generation showed significant differences between carriers and controls, between low (≤50%) and high (>50%) FIX:C carriers, and specifically in the TF + thrombomodulin model, between high FIX:C carriers and controls, although the BS were not different. Highlights: Amish Carriers had lower FIX:C, VWF:Ag and TAFI vs. controls but a similar mean bleeding score. Amish Carriers demonstrated lower TG parameters on mathematical models vs. controls. Amish Carriers with FIX:C ≤ 50% had lower TG curves vs. FIX:C > 50% but similar BS.